Antecedents of impulse buying behaviour in generation z - Sagitarini, Ni Km Tri Sukma; Martini, Ida Ayu Oka (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to determine how impulse buying behaviour is influenced by customer reviews and influencer credibility, using trust as a mediating factor in the purchase of skintific products by generation z in Bali province. Method – An online survey was used to collect quantitative data from 210 respondents selected using purposive sampling. The study population comprises generation z individuals in Bali who have purchased skintific products online. Structural equation modeling-partial least squares (SEM-PLS) was used to analyse the data to see the direct and indirect interactions between variables. Findings – The results revealed that customer reviews do not affect impulse buying behavior. Influencer credibility positively affects impulse buying behaviour. In addition, customer reviews positively affect trust, while influencer credibility does not affect trust. Furthermore, trust positively affects impulse buying behavior. In terms of mediation, trust fully mediates the relationship between customer reviews and impulse buying behaviour. Meanwhile, trust does not mediate the relationship between influencer credibility and impulse buying behaviour. Implications – Theoretically, these findings enrich the literature regarding factors influencing impulse buying behaviour by highlighting the mediating role of trust in the relationship between customer reviews and purchase decisions. Practically, the findings in this study suggest that brands should improve the quality of customer reviews to strengthen consumer trust, while influencer marketing strategies should focus on emotional engagement and interactive content.